2023
DOI: 10.1101/2023.10.13.23292651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design and selection of drug properties to increase the public health impact of next-generation seasonal malaria chemoprevention: a modelling study

Lydia Braunack-Mayer,
Josephine Malinga,
Thiery Masserey
et al.

Abstract: BackgroundSeasonal malaria chemoprevention (SMC) is recommended for disease control in settings with moderate to highPlasmodium falciparumtransmission and currently depends on administration of sulfadoxine-pyrimethamine with amodiaquine. However, poor regimenadherence and the increasedfrequencyof sulfadoxine-pyrimethamine resistant parasite mutations may threaten SMC’s effectiveness. We need guidance to de-risk the development of drug compounds for malaria prevention.MethodsWe combined an individual-based mala… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…11 This may be attributed to the high drug e cacy of the SMC treatment combination. 11,29 Despite concerns that the e cacy of SP may be undermined by drug resistance, 10,[30][31][32] SMC continues to be proven effective in different settings. 10,12,33 The consistent rise in rates of both uncomplicated and severe malaria from the third to the fourth week post administration of each round suggests that the effect of SMC is short-lived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This may be attributed to the high drug e cacy of the SMC treatment combination. 11,29 Despite concerns that the e cacy of SP may be undermined by drug resistance, 10,[30][31][32] SMC continues to be proven effective in different settings. 10,12,33 The consistent rise in rates of both uncomplicated and severe malaria from the third to the fourth week post administration of each round suggests that the effect of SMC is short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…35 SMC drug e cacy, coverage level and duration of protection are among the most important factors that determine its effectiveness for malaria prevention and control. 31 A modeling study found that the duration of protection of SMC has higher importance for its public health impact on preventing disease than the drug's e cacy (parasite killing effect). 38 Therefore, for chemoprevention, as opposed to treatment, preventing infection throughout the high-risk period and between cycles was found more important than high curative e cacy.…”
Section: Discussionmentioning
confidence: 99%